Role as a Companion Facilitator at PT. BTPN Syariah Tbk in Certified Independent Study Internship (MSIB) to Develop Students Critical Thinking Skills - Permana, Arif; Prastyaningtyas, Efa Wahyu (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This study aims to explain the role of the Independent Learning Independent Dictionary(MBKM) internship program at BTPN Syariah as a facilitator for the development of students' critical thinking skills through internships.Design/Methode/Approach: The research used is qualitative descriptive qualitative with interview data collection techniques.Research Finding: The results of the study showed that students who participated in the internship program obtained the aim of examining the benefits of the Certified Independent Study Internship(MSIB) in developing students' critical thinking skills through the role of a companion facilitator in the internship program. Internship programs, particularly those involving the role of an accompanying facilitator, provide a unique opportunity for students to apply their knowledge and skills in real-world contexts.Theoretical contribution/Originality : This study makes significant theoretical contributions by examining how the Companion Facilitator role in PT. BTPN Syariah's MSIB program bridges experiential learning theory with practical workplace application in Islamic banking. Our findings demonstrate how structured mentoring, real-world problem solving, and critical reflection in certified internships uniquely develop students' higher-order thinking skills - an underexplored dimension in conventional internship research. The research introduces an innovative framework that connects industry mentorship practices with cognitive skill development, offering new insights into optimizing industry-academic partnerships for more impactful experiential learning. This work particularly advances understanding of critical thinking cultivation in non-Western business contexts and Sharia-compliant financial environments.Practitionel/Policy implication : For higher education institutions, these findings emphasize the need to develop formal partnerships with industry players like PT. BTPN Syariah to design internship curricula that systematically cultivate critical thinking through mentored projects and reflective practice. Corporations should implement structured internship guidelines featuring analytical tasks and provide mentor training programs to maximize cognitive skill development. At the policy level, MSIB organizers should incorporate critical thinking metrics into program assessments and expand this model across sectors. Students should approach internships as active learning opportunities by engaging in challenging projects and reflective discussions. These recommendations collectively enhance the transformative potential of certified internship programs in developing future-ready graduates.Research limitations: This research has limitations such as peers who are only placed 1 student in each branch so that it is difficult to find students as respondents, so that the context may not be representative of students from other universities.kills